Type 2 Diabetes Mellitus Cascade of Care Among Saudi Adults: A Cross-Sectional Analysis of National Health Survey Data and Alignment With International Glycemic Control Targets - Ahmed A. Almohammadi; Hassan Almohammadi (University of Bisha Journal for Basic and Applied Sciences, 2026)
Background: Type 2 diabetes mellitus represents one of the most consequential noncommunicable diseases globally, yet substantial gaps in diagnosis, treatment, and glycemic control persist across all income settings. Saudi Arabia carries one of the highest diabetes burdens in the Eastern Mediterranean Region amid ongoing epidemiological transition.Objectives: To characterize the type 2 diabetes mellitus cascade of care — prevalence, awareness, treatment, and glycemic control — among Saudi adults and evaluate alignment with International Diabetes Federation and WHO glycemic control benchmarks.Methods: This cross-sectional descriptive study analyzed secondary data from the Saudi Health Interview Survey 2019 (SHIS-2019; n = 10,735 adults aged = 18 years), Saudi Ministry of Health Annual Statistical Yearbooks (2019–2023), and International Diabetes Federation Atlas regional estimates. Diabetes was defined as fasting plasma glucose = 7.0 mmol/L, HbA1c = 6.5%, or current antidiabetic medication use. Treatment was defined as current use of antidiabetic pharmacotherapy (oral agents and/or insulin). Cascade outcomes were analyzed by sex, age group, geographic region, and urban-rural classification. Descriptive statistics with 95% confidence intervals were calculated. STROBE guidelines were followed.Results: Overall diabetes prevalence was 18.3% (95% CI: 17.6–19.0%). Among diabetic adults, 69.4% were aware of their diagnosis; 84.2% of aware individuals were on pharmacological treatment; and 41.3% of treated individuals achieved glycemic control (HbA1c < 7.0% or, where HbA1c was unavailable, fasting plasma glucose